2021
DOI: 10.1007/s00354-021-00125-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of COVID-19 Under-Reporting in the Brazilian States Through SARI

Abstract: Due to its impact, COVID-19 has been stressing the academy to search for curing, mitigating, or controlling it. It is believed that under-reporting is a relevant factor in determining the actual mortality rate and, if not considered, can cause significant misinformation. Therefore, this work aims to estimate the under-reporting of cases and deaths of COVID-19 in Brazilian states using data from the InfoGripe. InfoGripe targets notifications of Severe Acute Respiratory Infection (SARI). The methodology is based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The key finding of 22.62% underestimation and corrected COVID-19 MR in Brazil in 2020 was based on the direct method, thus independent of the pre-epidemic data and eventual bias in the adjustment methods. Finally, a reasonable agreement between this result and that from the other two studies with the same scope [23,25] provides some reassurance as to the validity of the conclusion.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The key finding of 22.62% underestimation and corrected COVID-19 MR in Brazil in 2020 was based on the direct method, thus independent of the pre-epidemic data and eventual bias in the adjustment methods. Finally, a reasonable agreement between this result and that from the other two studies with the same scope [23,25] provides some reassurance as to the validity of the conclusion.…”
Section: Discussionsupporting
confidence: 78%
“…Another study found the mortality by natural causes in Brazil 22% higher than expected as of early June 2020 compared to the 2015-2019 period [27], which is equivalent to the excess MR of 125 per 100 000. The most recent publication on this topic [25] estimated 57 070 undisclosed COVID-19 deaths in 2020, corresponding to about 23% downward bias and COVID-19 MR of 117 per 100 000 compared with the Ministry of Health data [5]. As COVID-19 treatment advanced, its case fatality reduced and brought about lower mortality by the end of the year, as suggested in the present study.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In Brazil, one of the countries with the lowest number of tests performed in the world, the Ministry of Health confirmed the first case on 25 February 2020 and the first report of self-sustaining cases on 5 March 2020. Therefore, COVID-19 is significantly underreported, thus resulting in an increase in the number of symptomatic cases and hampering the application of effective public policies, mainly in terms of social restriction [4][5][6][7] . Moreover, information on socioeconomic, demographic and epidemiological determinants are not routinely investigated [8] .…”
Section: Introductionmentioning
confidence: 99%